The Effect of Giving Binahong Boiled Water on Blood Pressure in the Elderly in Jatisura Village RW 4, Cikedung District, Indramayu Regency - Rahayu (Indo Consultan Energi, 2023)
Hypertension is often referred to as the silent killer because it is a deadly disease without its symptoms as a warning to its victims. The therapy that can reduce hypertension is herbal therapy which is also proven to reduce blood pressure, such as binahong boiled water. The purpose of this study was to analyze the administration of binahong boiled water to blood pressure in the elderly in Jatisura Village RW 4, Cikedung District, Indramayu Regency, in 2022. This study design used a one-group pre-test and post-test design, with a population of 161 respondents and a sample of 61 respondents using sampling. Purposive sampling. Dependent variable blood pressure and independent binahong boiling water, data collection observation sheet. Statistical data analysis using the Wilcoxon test. The results of the univariate analysis before giving binahong boiled water for hypertension level 2 were 36 (58.1%). After giving binahong water for hypertension level 1, namely 35 (56.5%) with the Wilcoxon statistical test, it was found that the p-value was 0.000, which is greater than the value α = 0.05. The conclusion is that there is an effect of giving binahong leaf boiled water on blood pressure in the elderly in Jatisura Village RW 4, Cikedung District, Indramayu Regency, in 2022. Giving binahong leaves as an alternative treatment for people with high blood pressure